Odpowiedzi

2010-04-14T17:22:28+02:00
A)m*n-m+n dla m= -2, n=¾
-2* 3/4 - (-2) + 3/4= -3/2 +2 i 3/4 = -1 i 2/4 +2 i 3/4= 1 i 1/4
b)r²+s²-(r+s) dla r=-3, s=-2
(-3)²+ (-2)² - (-3+(-2))= 9 +4 +5= 18
1 5 1
2010-04-14T17:23:28+02:00
A)m*n-m+n dla m= -2, n=¾
-2* 3/4 - (-2) + 3/4= -3/2 +2 i 3/4 = -1 i 2/4 +2 i 3/4= 1 i 1/4

b)r²+s²-(r+s) dla r=-3, s=-2
(-3)²+ (-2)² - (-3+(-2))= 9 +4 +5= 18

proszę ;) mam nadzieje że dobrze i liczę na naj ;)
3 3 3
2010-04-14T17:23:30+02:00
A)m*n-m+n dla m= -2, n=¾
b)r²+s²-(r+s) dla r=-3, s=-2

a)-2 * ¾ -(-2) + ¾ = -3/2 +2¾ = -1 2/4 + 2¾ = 1¼

b)(-3)²+ (-2)²-(-3+(-2))= 9+4+5=18


1 3 1